Physical Characteristics of Analog Coffee from Kepok Banana Skin (Musa paradisiaca) Fermented with Lactobacillus plantarum - Anggun Desiana Sofa; Fafa Nurdyansyah; Umar Hafidz Asy’ari Hasbullah (International Journal of Advance Tropical Food, 2019)
Kepok banana peel can be used as analog coffee. The use of Lactobacillus plantarum is expected to be able to increase flavor during roasting. This study aims to study the effect of fermentation with L. plantarum and roasting time on physical characteristics and analog coffee preferences. This research uses factorial design with the first factor, fermentation, and non-fermentation, while the second factor is the roasting time of 10, 20, and 30 minutes. Kepok banana skin-fermented with L. plantarum for 4 days at 37°C. Drying banana peels done at a temperature of ±50°C for 24 hours. The roasting is done in 10, 20, and 30 minutes. Then milling and sifting are carried out. The results showed that the longer the roasting would decrease the L* value. Fermentation treatment will reduce the value of L*. The fermentation treatment will increase the panelists' liking for color and appearance.Keywords: analog coffee, kepok banana peel, L. plantarum , fermentation